# Solve for r 3(r-6)+2=4(r+2-21)

3(r-6)+2=4(r+2-21)
Simplify 3(r-6)+2.
Simplify each term.
Apply the distributive property.
3r+3⋅-6+2=4(r+2-21)
Multiply 3 by -6.
3r-18+2=4(r+2-21)
3r-18+2=4(r+2-21)
3r-16=4(r+2-21)
3r-16=4(r+2-21)
Simplify 4(r+2-21).
Subtract 21 from 2.
3r-16=4(r-19)
Apply the distributive property.
3r-16=4r+4⋅-19
Multiply 4 by -19.
3r-16=4r-76
3r-16=4r-76
Move all terms containing r to the left side of the equation.
Subtract 4r from both sides of the equation.
3r-16-4r=-76
Subtract 4r from 3r.
-r-16=-76
-r-16=-76
Move all terms not containing r to the right side of the equation.
Add 16 to both sides of the equation.
-r=-76+16
-r=-60
-r=-60
Multiply each term in -r=-60 by -1
Multiply each term in -r=-60 by -1.
(-r)⋅-1=(-60)⋅-1
Multiply (-r)⋅-1.
Multiply -1 by -1.
1r=(-60)⋅-1
Multiply r by 1.
r=(-60)⋅-1
r=(-60)⋅-1
Multiply -60 by -1.
r=60
r=60
Solve for r 3(r-6)+2=4(r+2-21)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top